Improving school counselors’ personal quality through collaboration with parents a phenomenological Study among school counselors in junior high schools - Purwaningrum, Ribut; Suryawati, Citra Tectona; Kholili, Ma'rifatin Indah (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to explore and describe the essence of collaboration activities conducted by school counselors with parents from the perspective of school counselors. This transcendental phenomenological study consisted of several stages: identifying phenomena, bracketing, data collection, data analysis, and data presentation. It involved six male and female school counselors from various junior high schools as participants. They have different backgrounds and lengths of service, allowing diverse interpretations of collaboration. Data were collected through in-depth interviews, supported by supplementary data. The results and discussions are categorized into four sections: existing collaboration programs in schools, the experiences of collaboration held by the counselors, the personal significance of collaboration, and the enhancement of personal quality acquired through collaboration. Future studies are recommended to explore efforts to enhance collaboration skills in prospective school counselors, the need for developing a digital platform for parent-school counselor collaboration, and the necessity of providing continuous training to school counselors to improve collaboration skills.